Seismicity overview of the Mohns Ridge and Knipovich Ridge 1955-2015 - Víkingur Logi Ásgeirsson 1991- (2015)
This thesis gives an overview of seismic activity on the Mohns and Knipovich ridges for the period of 1955-2015. Fault plane solutions on both ridges are dominated by normal faulting trending with the ridge axes. The Mohns Ridge is quite active and its seismicity is similar to that of large parts of the Mid-Atlantic Ridge, with earthquakes concentrated near the ridge's axis. The Knipovich Ridge is less active and shows less typical characteristics; seismic activity is not concentrated on the axis but is rather diffuse. One segment of the Knipovich Ridge shows anomalously high seismicity. The Jan Mayen Fracture Zone is very active seismically and normal, reverse, and strike-slip faulting is present. The Molløy Fracture Zone is not very active and strike-slip and normal faulting is present. Where each ridge connects to its respective fracture zone, there is a 20-30 km band of very little earthquake activity. Several large earthquakes were present in the data, the largest six of which (Mw >= 6.0) took place on the fracture zones and the Mohns Ridge. Few noteworthy earthquake swarms were observed. Intraplate earthquakes were mostly small and concentrated to the east of the ridges. Gutenberg-Richter b-values were calculated for each ridge, with the Mohns Ridge values ranging between 1.61 and 1.81 and Knipovich Ridge values ranging between 1.57 and 1.75. The Mohns Ridge showed no clear trend regarding the seismic moment, while the Knipovich Ridge shows a downward trend towards the north, aside from the one very active ridge segment near 76.35°N. The Jan Mayen Fracture Zone showed the highest normalized seismic moment of any segment in the area, while the Molløy Fracture Zone was among the lowest. Calculated ridge spreading rate and azimuth ranges from 14.38 mm/yr, 128.3° at the northern end of the Knipovich Ridge to 16.91 mm/yr, 114.7° at the southern end of the Mohns Ridge. Þessi ritgerð veitir yfirlit yfir jarðskjálftavirkni á Mohns og Knipovich hryggjum á tímabilinu 1955-2015. Brotlausnir á báðum hryggjum ...